2005
DOI: 10.1021/jp052913r
|View full text |Cite
|
Sign up to set email alerts
|

Probing Electric Fields at the Ionic Liquid−Electrode Interface Using Sum Frequency Generation Spectroscopy and Electrochemistry

Abstract: The arrangement of ions at the platinum electrode in the room-temperature ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate has been determined using sum frequency generation vibrational spectroscopy (SFG), electrochemical impedance spectroscopy (EIS), and the vibrational Stark effect. The results indicate that CO adsorbed on the Pt electrode has a Stark shift of 30-35 cm(-1)/V in the ionic liquid. The potential of zero charge (PZC) of the ionic liquid-Pt system is approximately -500 mV (vs Ag wire), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
183
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(206 citation statements)
references
References 44 publications
(71 reference statements)
22
183
0
1
Order By: Relevance
“…69 Negative temperat dence was observed for similar ILs and an Hg elec well as for molten salt electrolytes. 71 While Mo simulations, [72][73][74] modified MSA theory, 75 and DF have revealed that the DC can have both negative a temperature dependence for the restricted primitiv negative temperature dependence is expected for t and temperature of our simulations. that the use of single-frequency measurements could lead to misleading results [98][99][100] .…”
Section: B Capacitancementioning
confidence: 55%
“…69 Negative temperat dence was observed for similar ILs and an Hg elec well as for molten salt electrolytes. 71 While Mo simulations, [72][73][74] modified MSA theory, 75 and DF have revealed that the DC can have both negative a temperature dependence for the restricted primitiv negative temperature dependence is expected for t and temperature of our simulations. that the use of single-frequency measurements could lead to misleading results [98][99][100] .…”
Section: B Capacitancementioning
confidence: 55%
“…A study using imidazolium bistriflamide, (F 3 CSO 2 ) 2 N − and BF 4 − salts suggested that a model of alternating anion and cation layers may be applicable to the data [29,30]. Baldelli [31,32] concluded that the double layer is one ion layer thick using sum frequency generation spectroscopy and electrochemistry to probe the electric field at the ionic liquid/electrode interface. The double layer capacitance in an ionic liquid is considerably smaller than in an aqueous solution and less than that predicted by having a perfect Helmholtz layer at the interface, which could result from the presence of ion pairs at the electrode surface at all potentials.…”
Section: Why Use Ionic Liquids For Electrodeposition?mentioning
confidence: 99%
“…Despite the difficulties in precise alignment of the two incident beams through the solution phase and the very expensive and sophisticated equipment, successful application of SFG spectroscopy in studies of the electrode/ionic liquid interface has been performed. [30,47,[83][84][85][86][87] …”
Section: In Situ Characterizationmentioning
confidence: 99%